IDENTIFIKASI TENTANG PENGGUNAAN BAHAN AJAR PADA MATA PELAJARAN AKUNTANSI KELAS X AKUNTANSI DI SMK NEGERI 1 JOMBANG - EKA MUFLICHA WARDANI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
One of the things that need to be observed in the process of learning through teaching materials is the extent to which the material in the teaching materials can be understood by learners. Results of the study indicate that teaching materials expert teaching materials such as textbook otherwise feasible for use in learning. On the basis of competence compiling financial reports 74.57% as large as feasible, to record a journal cover basic competence as feasible as big as 74.86%, and compiling a list of basic competence account after closing 74.86% as large as feasible. Modules form of teaching materials as feasible. On the basis of competence compiling financial reports qualify as large as 76.69%, chronicle journal cover basic competence qualify as big as 76.69%, and basic competence compile the list of eligible account balance after closing big as 76.40%. From the responses of the students on the use of otherwise good accounting teaching materials. Results show the percentage of basic competence compiling financial reports as big as 77.62%, basic competence chronicle journal size cover 78.93% and compiling a list of basic competence account balance after closing big as 78.21%. Keywords: Teaching Material, Accounting Lesson